1994
DOI: 10.1001/jama.1994.03520170068038
|View full text |Cite
|
Sign up to set email alerts
|

Acute Epiglottitis in Adults

Abstract: Most adults who have acute epiglottitis can be managed conservatively and have low morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0
13

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(67 citation statements)
references
References 11 publications
4
49
0
13
Order By: Relevance
“…Unlike the case of the pediatric age group, the causative microbiological agent in adults is not easily identified, and the seasonal differences in the incidence of infection in adults are not as pronounced as they are in children (11). In our study, bacterial cultures were only taken from five patients, and one patient showed S. pneumoniae growth.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Unlike the case of the pediatric age group, the causative microbiological agent in adults is not easily identified, and the seasonal differences in the incidence of infection in adults are not as pronounced as they are in children (11). In our study, bacterial cultures were only taken from five patients, and one patient showed S. pneumoniae growth.…”
Section: Discussionmentioning
confidence: 79%
“…Although it is common in children between the age of 2 and 5 years, it can also be seen in adults. In adults, it is common in males between the age of 30 and 70 years (11). Epidemiological studies have shown that the number of acute epiglottitis cases has decreased in children due to proper vaccinations, while the number of adult cases has increased significantly (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Controversy persists concerning airway management of previously healthy adults with epiglottitis. 6 Some investigators have recommended that most patients with mild to moderate signs and symptoms of airway compromise may be managed conservatively with careful monitoring, 5,15,16 while others have argued that elective endotracheal intubation is a safer approach 8,17 based on a variety of clinical predictors. 5,[17][18][19] Despite this relative debate, it is intuitively obvious that immediate airway intervention is required for adults with acute epiglottitis and impending airway obstruction, including our patient.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Most commonly, blood cultures remain negative in patients with adult epiglottitis, 5,8,12 and cultures obtained directly from the epiglottitis and surrounding tissue during laryngoscopy also fail to identify the responsible bacterial pathogen. 7 As a result of these data, blood, epiglottic, and oropharyngeal cultures were not obtained in our patient and instead, empiric treatment with a broad-spectrum intravenous antibiotic (piperacillin-tazobactam) was instituted in order to provide coverage against H. influenzae, Streptococcus species, and Corynebacterium diphtheriae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation